2021
DOI: 10.1097/ju.0000000000001836
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Post-Treatment Kidney Stone Fragments: A Systematic Review and Meta-Analysis

Abstract: Purpose: We assessed the literature around post-treatment asymptomatic residual stone fragments and performed a meta-analysis. The main outcomes were intervention rate and disease progression. Materials and Methods: We searched OvidÒ, MEDLINEÒ, EmbaseÔ, the Cochrane Library and ClinicalTrials.gov using search terms: "asymptomatic", "nephrolithiasis", "ESWL", "PCNL", "URS" and "intervention." Inclusion criteria were all studies with residual renal fragments following treatment (shock wave lithotripsy, ureterosc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“… 56 In a recent meta-analysis, Brain et al evaluated literature regarding natural history of post-treatment renal stone fragments and concluded that patients with residuals >4 mm carry a significantly increased risk of intervention compared to fragments ≤4 mm. 57 Disease progression did not differ significantly between the two groups. 57 The EAU Guideline Urolithiasis Panel performed a systematic appraisal of the literature, concluding that for residuals ≤4 mm intervention was in the range 17–29%, disease progression 9–34% and spontaneous expulsion 21–34% during 4 years of follow-up, while for fragments >4 mm, intervention was in the range 24–100%.…”
Section: Clinically Insignificant Residual Fragments (Cirfs) After St...mentioning
confidence: 85%
See 1 more Smart Citation
“… 56 In a recent meta-analysis, Brain et al evaluated literature regarding natural history of post-treatment renal stone fragments and concluded that patients with residuals >4 mm carry a significantly increased risk of intervention compared to fragments ≤4 mm. 57 Disease progression did not differ significantly between the two groups. 57 The EAU Guideline Urolithiasis Panel performed a systematic appraisal of the literature, concluding that for residuals ≤4 mm intervention was in the range 17–29%, disease progression 9–34% and spontaneous expulsion 21–34% during 4 years of follow-up, while for fragments >4 mm, intervention was in the range 24–100%.…”
Section: Clinically Insignificant Residual Fragments (Cirfs) After St...mentioning
confidence: 85%
“… 57 Disease progression did not differ significantly between the two groups. 57 The EAU Guideline Urolithiasis Panel performed a systematic appraisal of the literature, concluding that for residuals ≤4 mm intervention was in the range 17–29%, disease progression 9–34% and spontaneous expulsion 21–34% during 4 years of follow-up, while for fragments >4 mm, intervention was in the range 24–100%. 58 Raman et al evaluated patients with residuals after percutaneous nephrolithotomy (PNL) and found that patients with fragments 2–4 mm experienced more symptomatic episodes and re-interventions compared to those with fragments <2 mm.…”
Section: Clinically Insignificant Residual Fragments (Cirfs) After St...mentioning
confidence: 85%
“…However, more recently, this has been challenged. These residual fragments are likely to become clinically significant [27], and therefore the definition of ‘stone free’ has been redefined to ‘no fragments’. This ambiguity about stone free ascertainment and definition are the likely reasons behind poor prediction.…”
Section: Discussionmentioning
confidence: 99%
“…However, the latest studies show that in some patients, postoperative small residual stones fragments are not expelled and may lead to stone-related symptoms such as infection, hematuria, back pain, and even require surgical treatment [5][6][7][8]. In addition, the probability of stone growth in patients with upper urinary tract stones after surgery is 10% within 1 year, 35% within 5 years, and up to 50% within 10 years [9,10].…”
Section: Introductionmentioning
confidence: 99%